Impact of Power Loom Industry During Covid- 19 Pandemic Period Major District in Tamilnadu - et. al., Dr.S. Prakash, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indian textile industry is as diverse a complex as country itself and it combines with equal equanimity this immense diversity into a cohesive whole. The world is battling with modern horrors like the COVID-19, which has left the entire world befuddled and in the lurch as to how one virus has brought the entire world to a standstill. This devastating virus which is declared by the WHO as the pandemic has taken over almost 195 countries in its grip. The entire world is facing Covid-19 Pandemic, which has not left any part of the world to face it. One side lives are been lost as a result of Pandemic, on the other side largest problem that the world is facing big downfall in the economy too. The objectives of the paper to find out the economic crisis have attacked various businesses in and around the world during the pandemic period . In all sorts of Travel, Hospitality, Hotels, Restaurants, Bar, Package food, retail, e- commerce, Automobile etc. One of the severely affected industries is Textile manufacturing too which is the second largest employment creating industry after agriculture. The textile and clothing Industry employs over 105 million people and also earn around US 40 billion FOREX, apart from substantial revenue under GST and other taxes. But this industry is shut down since due to lockdown and all the stakeholders of the industry are suffering severely. In Tamilnadu Textile Industry has three main segments mill sector, handloom sector and decentralized power loom sector. This paper analyses the impact of Power Loom Industry during the Covid- 19 Pandamic Period in Tamilnadu.